A Critical Introduction to International Criminal Law - Stahn, Carsten (Social Sciences, 2018)
Suitable for students, academics and professionals from multiple fields wishing to understand contemporary theories, practices and critiques of international criminal law, this book presents the field in an accessible way via five core themes: crimes, theories of responsibility, global justice institutions, procedures and punishment and reparation. This title is also available as Open Access on Cambridge Core.